Adjuvant radiotherapy for endometrial cancer with cervical stromal involvement: A patterns of practice survey in Australia and New Zealand. Issue 1 (11th October 2020) - Lapuz, Carminia; Govindarajulu, Geetha; Tacey, Mark; Lim, Adeline; Johnson, Carol
Abstract: Introduction: The purpose of this study is to describe the patterns of practice in Australia and New Zealand for post‐operative radiotherapy in endometrial cancer with cervical stromal involvement. Methods: A ten‐item survey including five clinical case scenarios in endometrial cancer with cervical stromal invasion was emailed to Royal Australian and New Zealand College of Radiologists (RANZCR) radiation oncologists in 2018. Responses were analysed to determine relative frequency distributions and preferred adjuvant treatment modalities for the clinical case scenarios. Results: A total of 65 respondents initiated the survey with 27 respondents treating more than 11 endometrial cancer cases annually. Only 31 respondents answered all five clinical case scenarios. Preferred adjuvant radiotherapy modalities varied for the Stage II cases between vault brachytherapy (VB), pelvic external beam radiotherapy (EBRT) or a combination. For the stage IIIA and IIIC1 cases, the majority recommended pelvic EBRT with or without VB boost (79% and 77%), and of these, most combined with chemotherapy (61% and 88%). For 4 of the 5 case scenarios, when pelvic EBRT was offered, most recommended a VB boost. Conclusion: This patterns of practice survey suggests variability in adjuvant radiotherapy recommendations in endometrial cancer with cervical involvement, particularly in cases where there is lack of randomised data and discrepancies in consensus guidelines.